Oral 11β-HSD1 inhibitor AZD4017 improves wound healing and skin integrity in adults with type 2 diabetes mellitus: a pilot randomized controlled trial. Issue 4 (28th February 2022) - Ajjan, R A; Hensor, E M A; Del Galdo, F; Shams, K; Abbas, A; Fairclough, R J; Webber, L; Pegg, L; Freeman, A; Taylor, A E; Arlt, W; Morgan, A W; et al.
Abstract: Background: Chronic wounds (e.g. diabetic foot ulcers) reduce the quality of life, yet treatments remain limited. Glucocorticoids (activated by the enzyme 11β-hydroxysteroid dehydrogenase type 1, 11β-HSD1) impair wound healing. Objectives: Efficacy, safety, and feasibility of 11β-HSD1 inhibition for skin function and wound healing. Design: Investigator-initiated, double-blind, randomized, placebo-controlled, parallel-group phase 2b pilot trial. Methods: Single-center secondary care setting. Adults with type 2 diabetes mellitus without foot ulcers were administered 400 mg oral 11β-HSD1 inhibitor AZD4017 ( n = 14) or placebo ( n = 14) bi-daily for 35 days. Participants underwent 3-mm full-thickness punch skin biopsies at baseline and on day 28; wound healing was monitored after 2 and 7 days. Computer-generated 1:1 randomization was pharmacy-administered. Analysis was descriptive and focused on CI estimation. Of the 36 participants screened, 28 were randomized. Results: Exploratory proof-of-concept efficacy analysis suggested AZD4017 did not inhibit 24-h ex vivo skin 11β-HSD1 activity (primary outcome; difference in percentage conversion per 24 h 1.1% (90% CI: −3.4 to 5.5) but reduced systemic 11β-HSD1 activity by 87% (69–104%). Wound diameter was 34% (7–63%) smaller with AZD4017 at day 2, and 48% (12–85%) smaller after repeat wounding at day 30. AZD4017 improved epidermal integrity but modestly impaired barrier function. Minimal adverse events were comparable to placebo. Recruitment rate, retention, and data completeness were 2.9/month, 27/28, and 95.3%, respectively. Conclusion: A phase 2 trial is feasible, and preliminary proof-of-concept data suggests AZD4017 warrants further investigation in conditions of delayed healing, for example in diabetic foot ulcers. Significance statement: Stress hormone activation by the enzyme 11β-HSD type 1 impairs skin function (e.g. integrity) and delays wound healing in animal models of diabetes, but effects in human skin were previously unknown. Skin function was evaluated in response to treatment with a 11β-HSD type 1 inhibitor (AZD4017), or placebo, in people with type 2 diabetes. Importantly, AZD4017 was safe and well tolerated. This first-in-human randomized, controlled, clinical trial found novel evidence that 11β-HSD type 1 regulates skin function in humans, including improved wound healing, epidermal integrity, and increased water loss. Results warrant further studies in conditions of impaired wound healing, for example, diabetic foot ulcers to evaluate 11β-HSD type 1 as a novel therapeutic target forchronic wounds.